Protocol for generation of multicellular spheroids through reduced gravity - Dylan A. Zinn; Christine Mehner; Tushar Patel (STAR Protocols, 2023)
Summary: Multicellular spheroids are useful models for drug testing or studying tumor biology, but their production requires specialized approaches. Here, we present a protocol to produce viable spheroids by slow rotation around a horizontal axis using standard culture tubes. We describe steps for both seed and starter culture, and maintenance and expansion of spheroids. We detail assessment of spheroid size, count, viability, and immunohistochemistry. This protocol reduces gravitational forces that lead to cell clumping and is amenable to high-throughput use. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.